PEDESTRIAN BRIDGES AS ELEMENTS OF THE NEW URBAN IDENTITY OF CITIES (Advances in Civil and Architectural Engineering, 2021)
By the start of the 21st century, the majority of the world’s population was living in cities. Therefore, a top priority has been solving the problem of connecting parts of the city divided by traffic infrastructure in the shortest possible manner by using pedestrian paths. The aim of this study was to analyze, systematize, and typologically define the specific types of structures that make this possible, specifically pedestrian bridges located above roads and railway corridors. The primary and secondary requirements that must be met when designing a pedestrian bridge were identified, and an analysis and comparison of examples of constructed pedestrian bridges in Croatia and the world are herein presented. The results of this study enable the conclusion that, in recent times, in the age of the spectacle society and spectacle architecture, pedestrian bridges are simultaneously deemed architecture, engineering, and infrastructure projects. They are becoming new elements in a city’s image and contribute to the creation of a new urban identity. The original design of pedestrian bridges fosters the use of different construction systems and materials in accordance with technical and technological advancements in construction.